The Altman’s Z-Score Model as a Financial Distress Prediction Tool During Covid-19 Pandemic (Case Study of IDX Manufacturing Companies Period 2017-2022) - Wijayanti, Murti; Hady, Hamdy; Hakim, Luqman (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to analyze financial distress manufacturing industry on IDX for the period 2017-2022 which experiencing performance pressure due to Covid-19 pandemic with Altman Z-Score model. Potential financial distress is analyzed using financial ratios of productivity (EBIT to Total Assets), liquidity (Working Capital to Total Assets), activity (Sales to Total Assets), solvency (Market Value of Equity to Total Liabilities), and profitability (Retained Earnings to Total Assets). A quantitative descriptive research method using purposive sampling technique in determining 31 listed companies as a sample. The analysis results show the Altman Z-score model is able to predict financial distress conditions on IDX listed companies manufacturing industry sector before and during the Covid-19 pandemic for the 2017-2022 period, by using its five financial ratios formulation as a tool.